2017
DOI: 10.1002/jcp.25976
|View full text |Cite
|
Sign up to set email alerts
|

The skeletal cell‐derived molecule sclerostin drives bone marrow adipogenesis

Abstract: The bone marrow niche is a dynamic and complex microenvironment that can both regulate, and be regulated by the bone matrix. Within the bone marrow (BM), mesenchymal stromal cell (MSC) precursors reside in a multi-potent state and retain the capacity to differentiate down osteoblastic, adipogenic, or chondrogenic lineages in response to numerous biochemical cues. These signals can be altered in various pathological states including, but not limited to, osteoporotic-induced fracture, systemic adiposity, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(132 citation statements)
references
References 56 publications
8
124
0
Order By: Relevance
“…Overall, there are a multitude of ways in which MAT and BMAs may contribute to tumor growth, and clinically targeting MAT is an interesting and innovative concept. It is possible that therapies that build bone may also inhibit MAT, as we have recently demonstrated with anti-sclerostin antibodies [54,57], and as others have found with PTH [47] and leptin [69]. The FGF family members may also hold promise for targeting to modulate not only bone, but also MAT.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Overall, there are a multitude of ways in which MAT and BMAs may contribute to tumor growth, and clinically targeting MAT is an interesting and innovative concept. It is possible that therapies that build bone may also inhibit MAT, as we have recently demonstrated with anti-sclerostin antibodies [54,57], and as others have found with PTH [47] and leptin [69]. The FGF family members may also hold promise for targeting to modulate not only bone, but also MAT.…”
Section: Discussionmentioning
confidence: 93%
“…Other researchers have shown that osteoclasts play a key role in determining if a myeloma cell will remain dormant or proliferate [49]. Osteocytes also dictate myeloma cell fate and bone remodeling [50–52], and we have shown that targeting osteocyte-derived sclerostin is an effective way to combat myeloma-induced bone disease in mouse models as well as decrease MAT [53,54]. …”
Section: Adipocyte and Adipokine Effects On Other Cells In The Tummentioning
confidence: 84%
See 1 more Smart Citation
“…Kennell and MacDougald investigated Xenopus Wnt8 and FZD1 or FZD2 chimeras and established a role for both β-catenin-dependent and β-catenin-independent mechanisms in mesenchymal cell fate and adipogenesis (57). Conversely, in a recent report, inhibition of Wnt signalling through the Wnt-inhibitory molecule sclerostin led to spontaneous adipogenesis of pre-adipocytes and mesenchymal precursors (58), supporting the concept of Wnt signalling controlling the adipogenic switch.…”
Section: Wnt/β-catenin Signalling In Liver Metabolismmentioning
confidence: 94%
“…61 Concurrent with increases in total body and visceral adiposity, high-fat diet models of obesity in rodents show increased marrow fat, 47,62 increased commitment to adipogenesis, and alterations in MSC differentiation potential. 63 MSC differentiation is also regulated by the Wnt signaling pathway, 6466 and it is understood that osteoblastogenesis and adipogenesis in the marrow generally maintain an inverse relationship. Adipocyte commitment is often associated with reduced bone formation, as seen in models of microgravity, 67,68 ovarian hormone depletion, 69,70 and aging.…”
Section: Impact Of Obesity On Musculoskeletal Tissue Systemsmentioning
confidence: 99%